Facile fabrication of mixed matrix membranes containing 6FDA-durene polyimide and ZIF-8 nanofillers for CO2 capture - Jusoh, N. (Korean Society of Industrial Engineering Chemistry, 2016)
Membrane separation has been used successfully in numbers of industrial applications especially in CO2 removal from CH4 because it's involved less energy consumption and low maintenance. The aim of this research is to fabricate ZIF-8/6FDA-durene mixed matrix membranes for enhancement of CO2 capture and consequently to optimize its fabrication method. The results showed that membrane fabricated using total dispersion duration of 3 h with filler priming procedure demonstrated homogenous distribution of ZIF-8 in 6FDA-durene matrix and improved the separation performance. Therefore, the membrane is potential for the large scale production via the method optimized in this work. Â© 2016 The Korean Society of Industrial and Engineering Chemistry